Lifetime Labor Supply in a Search Model of Unemployment - Leon J.H. Bettendorf; D. Peter Broer (Tinbergen Institute, 2003)
This paper investigates the age-dependency of participation andunemployment by integrating job search with intertemporal optimizing behaviorof finitely-lived households. We find that search frictions and tax ratesdistort the decisions of older workers to a much larger extent than that ofyoung workers. This finding provides an explanation of the observed fall ofparticipation rates of elder workers as a result of the post-war increase intax rates and replacement rates. We show that the age pattern of searchunemployment does not match observed unemployment and we propose a new conceptof 'voluntary' unemployment that agrees well with observations.
Keywords: J64; D91; J31; 330; search frictions; labor supply; life cycle; unemployment; retirement.; Arbeitsangebot; Arbeitsuche; Arbeitslosigkeit; Ältere Arbeitskräfte